Use of favipiravir in lactating mother with COVID-19 - Karabayır, Nalan; Öcal Doğan, Özlem; Canbeyli, Gülçin (AVES, 2021)
SARS-CoV-2 virus, which appeared in Wuhan, China in December 2019 and spread rapidly all over the world, affects children of all ages.1,2 During the COVID-19 pandemic, nursing mothers are worried about breastfeeding. Similar to CDC, the Turkish Ministry of Health and the Turkish Neonatal Society recommend that COVID-19 mothers breastfeed or express breast milk with necessary precaution.3,4 In 2 studies conducted with babies of COVID-19 mothers in our country, the rate of feeding with breast milk was found to be 43.2% in the first study, while it was 74% in the other study.5,6 One of the biggest concerns of breastfeeding mothers is that drug side effects may be seen in their babies. Various drug groups such as RNA polymerase inhibitors (favipiravir), HIV protease inhibitors, interferons, antibody treatments, and azithromycin are used in the treatment of COVID-19.7 In our country, there is no study about the passage of favipiravir, which is used as the first option in COVID-19 treatment, into breast milk. Sharing the experiences about the babies of mothers who continue to breastfeed while using favipiravir is important in preventing early weaning off breastfeeding.
Keywords: COVID-19; Lactating Mother; Favipiravir